Unraveling Rice Tolerance Mechanisms Against Schizotetranychus oryzae Mite Infestation - Buffon, Giseli; Blasi, Édina Aparecida dos Reis; Rativa, Angie Geraldine Sierra; Lamb, Thainá Inês; Gastmann, Rodrigo; Adamski, Janete Mariza; Schwambach, Joséli; Ricachenevsky, Felipe Klein; Heringer, Angelo Schuabb; Silveira, Vanildo; Lopes, Mara Cristina Barbosa; Sperotto, Raul Antonio (Frontiers in Plant Science, 2018)
Rice is the staple food for over half of the world’s population. Infestation of Schizotetranychus oryzae (Acari: Tetranychidae) causes great losses in rice productivity. To search for rice genotypes that could better tolerate S. oryzae infestation, we evaluated morphological and production parameters in brazilian cultivars, and identified two cultivars with contrasting responses. Leaf damage during infestation was similar for all cultivars. However, infestation in Puitá INTA-CL resulted in reduction in the number of seeds per plant, percentage of full seeds, weight per 1,000 seeds, and seed length, whereas infestation in IRGA 423 increased weight per 1,000 seeds and seed length. Reduction in seed weight per plant caused by infestation was clearly higher in Puitá INTA-CL (62%) compared to IRGA 423 (no reduction detected), thus Puitá INTA-CL was established as susceptible, and IRGA 423 as tolerant to S. oryzae infestation. Photosynthetic parameters were less affected by infestation in IRGA 423 than in Puitá INTA-CL, evidencing high efficiency of energy absorption and use. S. oryzae infestation also caused accumulation of H2O2, decreased cell membrane integrity (indicative of cell death) and accelerated senescence in leaves of Puitá INTA-CL, while leaves of IRGA 423 presented higher levels of total phenolics compounds. We performed proteomics analysis of Puitá INTA-CL and IRGA 423 leaves after seven days of infestation, and identified 60 differentially abundant proteins (28 more abundant in leaves of Puitá INTA-CL and 32 in IRGA 423). Proteins related to plant defense, such as jasmonate synthesis, and related to other mechanisms of tolerance such as oxidative stress, photosynthesis, and DNA structure maintenance, together with energy production and general metabolic processes, were more abundant in IRGA 423. We also detected higher levels of silicon (as amorphous silica cells) in leaves of infested IRGA 423 plants compared to Puitá INTA-CL, an element previously linked to plant defense, indicating that it could be involved in tolerance mechanisms. Taken together, our data shows that IRGA 423 presents tolerance to S. oryzae infestation, and that multiple mechanisms might be employed by this cultivar. These findings could be used in biotechnological approaches aiming to increase rice tolerance to mite infestation.